Traditions in world cinema - Badley, Linda; Palmer, R. Barton, 1946-; Schneider, Steven Jay, 1974- (Traditions in world cinema., 2006)
The core volume in the Traditions in World Cinema series, this book brings together a colourful and wide-ranging collection of world cinematic traditions - national, regional and global - all of which are in need of introduction, investigation and, in some cases, critical reassessment. Topics include: German expressionism, Italian neorealism, French New Wave, British new wave, Czech new wave, Danish Dogma, post-Communist cinema, Brazilian post-Cinema Novo, new Argentine cinema, pre-revolutionary African traditions, Israeli persecution films, new Iranian cinema, Hindi film songs, Chinese wenyi pian melodrama, Japanese horror, new Hollywood cinema and global found footage cinema. Key Features Includes a preface by Toby Miller. Each chapter covers a key world cinema tradition and is written by an expert in the field: Roy Armes, Nitzan Ben-Shaul, Peter Bondanella, Corey Creekmur, Adrian Danks, Peter Hames, Randal Johnson, Robert Kolker, Myrto Konstantarakos, Jay McRoy, Negar Mottahedeh, Richard Neupert, Christina Stojanova, J.P. Telotte, Stephen Teo. Traditions are examined from a wide range of views and include historical, social, cultural and industrial perspectives.